Conformers, Vibrational Spectra and Laser-induced Rotamerization - Fausto, Rui (1993)
A6 initio molecular orbital (MO) calculations with a 6-31G* basis set have been carried out for CH,CICOOH. Structures and energies of relevant conformations have been determined by gradient geometry refinement and some conformationally dependent geometry trends discussed. The results agree with reported experimental data and provide a good insight for the intramolecular interactions which determine the relative stability of the various conformers. The normal mode analysis based on the 6-31G* harmonic force field is used to review previous assignments of the vibrational spectra of the various conformers and to interpret previous experimental findings (A. Kulbida and A. Nosov, J. Mol. Struct., 1992, 265, 17) on the laser-induced rotamerization of the chloroacetic acid monomer trapped in an argon matrix